Impact of The Covid 19 Pandemic: Is There Overreaction in LQ 45 Stock? - Deden Rizal Riadi; Erna Garnia; T Tahmat Tahmat (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2023)
The Covid-19 pandemic has had an impact on various aspects of life, including the capital market which has caused a negative response on most stock exchanges around the world, including the Indonesia Stock Exchange. The Effecieny Market Hypothesis (EMH) explains that the price of a stock will always be reflected from the information available in the market or investors tend to be rational. However, dramatic events such as COVID-19 allow investors to overreact. The results showed that there was an overreaction in both winner and loser stocks in the LQ 45 group on the IDX in 3 months of observation since covid was announced as a pandemic. This overreaction is then followed by a price reversal even though it has not given a significant return after t+13 for both winner and losser stocks. The speed of price recovery (magnitude effect) after the price reversal on the loser stock is higher (faster) than the winner stock. The speed of this price recovery is significantly affected by the company's capital structure and share ownership of individual investors (local and foreign).